Designing multimodal texts in a girls' afterschool journalism club in rural Kenya. (4th March 2019) - Kendrick, Maureen; Early, Margaret; Chemjor, Walter
Abstract: Characteristic of the twenty-first century are new literacy practices that require users and producers to be fluent with the affordances of multiple modes across print and digital media. In under-resourced contexts such as East Africa, these complex new multimodal practices have not been well documented. In this paper, we explore the context of an afterschool journalism club in rural Kenya as an informal learning space for 32 adolescent girls to realize multimodal text design following our donation of a laptop, digital camera and voice recorder. Using ethnographic methods that positioned the girls as researchers of their own practices, we collaboratively documented the girls' changing social practices as they produced and designed videos in the context of their community and journalism club. As we proceeded through our analysis, we drew inspiration from Luke and Freebody's Four Resources Model for reading print texts and Serafini's reconceptualization of the Four Resources required for reading visual and multimodal texts, taking up their call to critique and reformulate the model within the rapidly changing context of twenty-first century literacy practices. Our study identifies the emergent and dynamic nested social practices of: (1) explorer, (2) participant-user, (3) performer, and (4) activist as integral to the design of videos.